Carp Il10a and Il10b exert identical biological activities in vitro, but are differentially regulated in vivo. (February 2017) - Piazzon, M. Carla; Wentzel, Annelieke S.; Wiegertjes, Geert F.; Forlenza, Maria
Abstract: We recently reported on the functional characterization of carp Il10. We showed that carp Il10 is able to downregulate proinflammatory activities by carp phagocytes and promote B cell proliferation, differentiation and antibody production as well as proliferation of memory T cells. Taking advantage of the recent annotation of the carp genome, we completed the sequence of a second il10 paralogue, named il10b, the presence of which was expected owing to the recent (8 million years ago) fourth round of whole genome duplication that occurred in common carp. In the present study we closely compared the two Il10 paralogues and show that Il10a and Il10b have almost identical gene structure, synteny, protein sequence as well as bioactivity on phagocytes. Although the two il10 paralogues show a large overlap in tissue expression, il10b has a low constitutive expression and is highly upregulated upon infection, whereas il10a is higher expressed under basal conditions but its gene expression remains constant during viral and parasitic infections. This differential regulation is most likely due to the observed differences in their promoter regions. Altogether our results demonstrate that gene duplication in carp, although recent, led to sub-functionalization and expression divergence rather than functional redundancy of the Il10 paralogues, yet with very similar protein sequences. Highlights: Two paralogues of carp interleukin-10 are present and expressed. Il10a and Il10b have similar gene structure and protein sequence. Il10a and Il10b have similar bioactivity but are differentially regulated. il10a is highly expressed under basal conditions while il10b is regulated upon infection.